Spirituality and religiosity in combating pain - Camilla Domingues do Lago – Rizzardi; Manoel Jacobsen Teixeira; Silvia Regina Dowgan Tesseroli de Siqueira (O Mundo da Saúde)
The International Association for the Study of Pain defines pain as an unpleasant sensory and emotional experience, peculiar, specific and non transferable associated with actual or potential tissue damage. Pain, especially when chronic, affects all areas of life of individuals, being thus physical, psychic, and social. Amongst the forms for combating pain, religiosity and spirituality has proved to be important for sick people, and are related to the reduction of stress pain involves. The role and the mechanisms by which religiosity and spirituality act in combating chronic pain were the object of a literature survey in Medline database. Religiosity is characterized as the first or the second strategy used against pain. Religious and spiritual individuals present a reduction of pain complaints, of the concentration of ACTH (adrenocorticotropic hormone) and serous cortisol, a reduction of systolic arterial pressure, and cardiac and respiratory frequency. Religious activities produce an increase of the activation of prefrontal cortex, causing a higher efficiency and interactivity of hypothalamic-pituitary-adrenal system. The increase of pain mediators involved also occurs: GABA, serotonin and dopamine. Spiritual individuals face pain better, especially chronic pain, due to physiological and neural alterations coming from their beliefs.